Displaying time series, spatial, and space-time data with R - Perpiñán Lamigueiro, Óscar (Chapman & Hall/CRC the R series, 2014)
Focusing on the exploration of data with visual methods, Displaying Time Series, Spatial, and Space-Time Data with R presents methods and R code for producing high-quality graphics of time series, spatial, and space-time data. Practical examples using real-world datasets help you understand how to apply the methods and code. The book illustrates how to display a dataset starting with an easy and direct approach and progressively adding improvements that involve more complexity. Each of the book's three parts is devoted to different types of data. In each part, the chapters are grouped according to the various visualization methods or data characteristics.